2010
DOI: 10.1007/s00038-010-0138-3
|View full text |Cite
|
Sign up to set email alerts
|

Social capital as a determinant of self-rated health and psychological well-being

Abstract: Our findings suggest that trust and reciprocity and social participation and networks contribute to good self-rated health and psychological well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
97
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 43 publications
10
97
0
7
Order By: Relevance
“…Social relationships have a well-known protective effect on health and well-being, while social isolation is predictor of morbidity and mortality (Nieminen et al 2010;Pantell et al 2013;Yang et al 2016). Green space can play an important role in fostering social interactions and promote a sense of community that is essential for social cohesion (Kim and Kaplan 2004) as well as for human health (Lengen and Kistemann 2012).…”
Section: Improved Social Capital and Cohesionmentioning
confidence: 99%
“…Social relationships have a well-known protective effect on health and well-being, while social isolation is predictor of morbidity and mortality (Nieminen et al 2010;Pantell et al 2013;Yang et al 2016). Green space can play an important role in fostering social interactions and promote a sense of community that is essential for social cohesion (Kim and Kaplan 2004) as well as for human health (Lengen and Kistemann 2012).…”
Section: Improved Social Capital and Cohesionmentioning
confidence: 99%
“…These elements foster social cohesion and cooperation with several beneficial outcomes. Research has found that beneficial health outcomes are associated with having trust in others (Fujiwara & Kawachi, 2008;Giordano & Lindström, 2010;Hyyppä et al, 2007;Nieminen et al, 2010;Poortinga, 2006;Snelgrove et al, 2009;Tampubolon et al, 2011), socializing with friends, relatives, colleagues or neighbours (Veenstra, 2000;Ziersch, 2005), and participating in associations (Giordano & Lindström, 2010;Giordano et al, 2011;Hyyppä et al, 2007;Lindström et al, 2004;Nieminen et al, 2010;Poortinga, 2006). However, the evidence for the health benefits of norms of reciprocity and mutual aid is inconclusive (Fujiwara & Kawachi, 2008;Giordano et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Se ha demostrado la existencia de relaciones entre el bienestar mental y otras variables tales como desarrollo juvenil (Park, 2004), participación social (Nieminen, Martelin, Koskinen, Aro, Alanen, & Hyyppä, 2010), competencia emocional (Nelis, Kotsou, Quoidbach, Hansenne, Weytens, Dupuis, & Mikolajczak, 2011), salud física y mental (Zhang, Chen, McCubbin, McCubbin, & Foley, 2011), planificación del tiempo libre (Adams, Leibbrandt, & Moon, 2011) y longevidad (Diener & Chan, 2011), afirmando el valor heurístico del término (Tay & Diener, 2011;Diener, 2012).…”
Section: Introductionunclassified